2003
DOI: 10.2166/wh.2003.0023
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for microbial source tracking: Lessons from a methods comparison study

Abstract: The methods comparison study described in accompanying manuscripts demonstrated the potential value of microbial source tracking (MST) techniques, but also identified a need for method refinement. This paper provides three classes of recommendations to improve MST technology: optimization, development and evaluation. Optimization recommendations focus on library-dependent methods and include improved selection of restriction enzymes or antibiotics, better definition of appropriate library size, selection of ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 24 publications
1
41
0
2
Order By: Relevance
“…appear promising, since these markers are a sensitive measure of fecal pollution, are relatively simple to detect, and have been shown to be host specific (10,11). Further work is necessary to assess the informational value of detecting these markers in the environment and to determine their association with pollution sources (8,11,24,32,34). Extensive field testing will be necessary to determine the geographical distribution of source-specific genetic markers and their correlation with standard fecal indicators (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…appear promising, since these markers are a sensitive measure of fecal pollution, are relatively simple to detect, and have been shown to be host specific (10,11). Further work is necessary to assess the informational value of detecting these markers in the environment and to determine their association with pollution sources (8,11,24,32,34). Extensive field testing will be necessary to determine the geographical distribution of source-specific genetic markers and their correlation with standard fecal indicators (2).…”
Section: Discussionmentioning
confidence: 99%
“…Zoonotic reservoirs (including cattle, swine, and chickens) of pathogens are also of high concern (24). There are a wide variety of microbial-source tracking approaches under development, and a single approach may not be adequate, since all these methods have limitations (30,31,34). Culture-independent, molecular methods detect genetic targets of organisms found in a specific host.…”
mentioning
confidence: 99%
“…In contrast, other strains, such as RYC 2056, detect similar numbers of phages in different geographical areas but do not discriminate between the sources of fecal pollution (5,7,18,22). Strains tested in the United States to date appear to behave like RYC 2056 (15).Limitations of existing source tracking methods (19,24,25,26,27), combined with the good source tracking performance of strain HSP40 in certain geographical areas (4,9,12,28,30), along with increasing information about the specificity between the animal host and the bacteria of the Bacteroides group (11, 32) and the narrow host ranges reported for phages infecting Bacteroides (6,8,16,22,30), prompted our search for new Bacteroides host strains.We describe here a rapid method for isolating and further testing Bacteroides host strains potentially useful for source tracking.Isolation of new hosts for phages infecting Bacteroides. Four trials for isolation of Bacteroides strains from raw municipal sewage from Spain (two trials), Colombia (one trial), and the United Kingdom (one trial) were carried out by two independent operators.…”
mentioning
confidence: 99%
“…The ARA approach is based on the premise that fecal indicator bacteria (FIB) from hosts exposed to antibiotics will develop resistance to those antibiotics, and on the hypothesis that this selective pressure would be a mechanism for discriminating among fecal indicator bacteria from a variety of hosts [30][31][32][33][34][35]. A library or database composed of antibiotic resistance profiles (ARP) of FIB from known host sources is developed and serves as a point of reference for identifying unknown source isolates from water sources.…”
Section: Introductionmentioning
confidence: 99%
“…Two source tracking methods comparison studies reported issues with accuracy for numerous source tracking methods, including ARA. However, both studies also described approaches that could compensate for potential problems [35,36]. Such approaches include the application of cross-validation analysis of known-source isolates as well as the removal of clonal isolates to ensure a reliable library.…”
Section: Introductionmentioning
confidence: 99%